Marital Satisfaction and Social Desirability Bias - Edwin Adrianta Surijah; Daniel Yogi Prakasa (Jurnal Ilmiah Psikologi MIND SET, 2020)
Marital satisfaction is a critical variable in marriage study at large. However, there is not a single study investigating the influence of social desirability bias toward participants’ responses filling in the marital satisfaction scale in the Indonesian context. This study aims to determine which marital satisfaction scale free from bias. Participants of this study were 250 married couples who filled in three different marital satisfaction scales (Satisfaction with Married Life, Relationship Assessment Scale, and Perceived Relationship Quality Component). Regression analysis examined the contribution of social desirability bias toward marital satisfaction. Results showed that Satisfaction with Married Life scale is free from social desirability bias. Meanwhile, Relationship Assessment Scale and Perceived Relationship Quality Component were influenced by the social desirability. This study hopes to contribute to the Indonesian marriage study by utilizing a social desirable bias-free scale or by statistically controlling the bias.